2018
DOI: 10.1007/jhep09(2018)048
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of near-extremal black holes

Abstract: We analyse the dynamics of near-extremal Reissner-Nordström black holes in asymptotically four-dimensional Anti de Sitter space (AdS 4 ). We work in the spherically symmetric approximation and study the thermodynamics and the response to a probe scalar field. We find that the behaviour of the system, at low energies and to leading order in our approximations, is well described by the Jackiw-Teitelboim (JT) model of gravity. In fact, this behaviour can be understood from symmetry considerations and arises due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
261
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(266 citation statements)
references
References 72 publications
5
261
0
Order By: Relevance
“…where we defined 18) and c 0 is an integration constant, independent of the spacetime coordinates. Now we examine the dilaton equation of motion (5.13).…”
Section: (516)mentioning
confidence: 99%
See 1 more Smart Citation
“…where we defined 18) and c 0 is an integration constant, independent of the spacetime coordinates. Now we examine the dilaton equation of motion (5.13).…”
Section: (516)mentioning
confidence: 99%
“…And so the persistent trend in nAdS 2 holography, coined with a 'n' since we are 'near' to our original configuration, is that the deviations away from extremality are controlled by this pattern. For a review see [14].The application of this new framework to black hole physics has shown that, while JT models capture common features [15][16][17][18][19][20], the additional parameters for more general black holes display interactions that are not present in JT gravity [21][22][23][24][25][26][27]. This makes clear that there is new phenomena to be explored, that simpler models do not take into account.Our interest therefore is to further explore the properties of nAdS 2 /nCFT 1 with the goal of building a more refined understanding of the dynamics near the horizon of (near-)extremal black holes.…”
mentioning
confidence: 99%
“…It is an open question to account for non-extremal black hole entropy from dual field theory. If the qCGHS model can be embedded in higher dimensional black holes, one can hope to gain a better understanding of non-extremal black holes along the line of recent developments [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Among many other interesting papers, partial references include[17][18][19][20][21][22][23]. We apologize for our ignorance about any other important works.…”
mentioning
confidence: 99%
“…To that end, such alternate descriptions as the Jackiw-Teitelboim gravity, AdS 3 , and a certain 2 + 1-dimensional Kaluza-Klein compactification have all been proposed as purported candidates for the bulk dual [28][29][30][31][32][33][34][35][36].…”
Section: Original Syk Modelmentioning
confidence: 99%